Rare bird documentation form for Glaucous Gull at Lock and Dam 14 near Davenport, 1979 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1979)
Rare bird documentation form for a Glaucous Gull at Lock and Dam 14 near Davenport in Scott County, IA on December 16, 1979. Epson - sheet feed